ANALISIS SPASIAL PENYEBARAN PENYAKIT SCHISTOSOMIASIS MENGGUNAKAN INDEKS MORAN UNTUK MENDUKUNG ERADIKASI SCHISTOSOMIASIS DI PROVINSI SULAWESI TENGAH BERBASIS WEB DASHBOARD - Nur Sakinah; Wawan Saputra; Nurfitra Nurfitra; Satriani Satriani; Junaidi Junaidi (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
Schistosomiasis is a parasitic disease which is caused by worm infection with worms from the Schistosoma class. This disease is zoonotic, consequently the source of transmission is not only infected on mammals but also on humans. The method used in this study is spatial autocorrelation. This is conducted to determine the presence or absence of global or local spatial autocorrelation as well as the pattern distribution of Schistosomiasis cases in Poso Regency by using Moran's I. The result in this study showed that the p-value of positive global autocorrelation is 2,2 × 10-16. This result is smaller than the 5% of significance level and also smaller than the Moran's I value (0,66). The Moran’s I value lies in the interval indicating that each adjacent area has the same number of Schistosomiasis cases. Meanwhile, the local spatial autocorrelation test (LISA) for Schistosomiasis cases in Poso Regency, such as villages at Lore Utara, Lore Timur and Lore Peore has the LISA value 1 determining the correlation is strong and positive. The distribution pattern of Schistosomiasis cases in Poso Regency forms a group pattern, namely disease prone areas (HH), disease spread areas (HL), disease alert areas (LH) and disease safe areas (LL)